2021
DOI: 10.3390/jcm10091827
|View full text |Cite
|
Sign up to set email alerts
|

Genomics of Viral Hepatitis-Associated Liver Tumors

Abstract: Virus-related liver carcinogenesis is one of the main contributors of cancer-related death worldwide mainly due to the impact of chronic hepatitis B and C infections. Three mechanisms have been proposed to explain the oncogenic properties of hepatitis B virus (HBV) infection: induction of chronic inflammation and cirrhosis, expression of HBV oncogenic proteins, and insertional mutagenesis into the genome of infected hepatocytes. Hepatitis B insertional mutagenesis modifies the function of cancer driver genes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 123 publications
(185 reference statements)
0
3
0
1
Order By: Relevance
“…The molecular mechanism of TLK2 upregulation in HBVrelated HCC is not clear. Existing studies have shown that CIN is often observed in HBV-related HCC, which is associated with insertional mutations and the activation of cancer driver genes due to HBV DNA randomly integration into the host genome (Guichard et al, 2012;Seeger and Mason, 2015;Péneau et al, 2021). Highly genome-unstable tumors tended to overexpress TLK2 to achieve immune escape through suppressing cGAS-STRING-TBK1-mediated innate immune response (Segura-Bayona et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanism of TLK2 upregulation in HBVrelated HCC is not clear. Existing studies have shown that CIN is often observed in HBV-related HCC, which is associated with insertional mutations and the activation of cancer driver genes due to HBV DNA randomly integration into the host genome (Guichard et al, 2012;Seeger and Mason, 2015;Péneau et al, 2021). Highly genome-unstable tumors tended to overexpress TLK2 to achieve immune escape through suppressing cGAS-STRING-TBK1-mediated innate immune response (Segura-Bayona et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…HBV/HCV infections can induce genetic instability and have been shown to be important risk factors for HCC 27 , 28 . Several studies have suggested associations between serum FCN3 and FCN2 levels with HCV and HBV infections in patients with HCC 29 , 30 .…”
Section: Discussionmentioning
confidence: 99%
“…First, the integrated AAV sequence typically comprises transcription factor binding sites as well as viral enhancers [91], which causes an oncogene to be strongly overexpressed nearby (CCNE1 or TERT) [44,92]. Second, due to the usage of an alternate transcription start site (TSS) or the viral poly-A site, integrated viral sequences may cause the synthesis of truncated transcripts (for integrations in CCNA2 and TNFSF10, respectively) [93]. Remarkably, a region common to all inserted AAV sequences has recently been identified as a liver-specific enhancer-promoter element [91].…”
Section: Aav Infection and Hepatocellular Carcinomamentioning
confidence: 99%